2010
DOI: 10.1021/om100110p
|View full text |Cite
|
Sign up to set email alerts
|

Heteroselective Polymerization of rac-Lactide in the Presence of Dialkylgallium Alkoxides: The Effect of Lewis Base on Polymerization Stereoselectivity

Abstract: Well-defined dialkylgallium alkoxides derived from (S)-methyl lactate, (S,S)-[Me2Ga(μ-OCH(Me)CO2Me)]2 (1), and 2-methoxyethanol, [Me2Ga(μ-OCH2CH2OMe)]2 (2), have been used as model complexes for the ring-opening polymerization of lactide. (S,S)-[Me2Ga(μ-OCH(Me)CO2Me)]2 (1) can polymerize rac-lactide in solution in a living manner to give atactic polylactide (PLA). The addition of Lewis base to 1 gives heterotactically enriched polylactide at 40 °C, in CH2Cl2 with 6 equiv of THF (P r = 0.60, P r = probability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
73
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 41 publications
3
73
0
Order By: Relevance
“…As we were unable to isolate any stable alkoxide Me2InOR(6-Mes) complex, we focused on the activity of 1 in the ROP of rac-LA. Due to the reactivity of 1 towards CH2Cl2, which led to the almost quantitative and instant formation of [Me2Ga(μ-OCH2CH2OMe)]2 [9,35], no activity of 1 in the ROP of rac-LA in CH2Cl2, at −20 °C was observed. On the other hand, the polymerization of rac-LA with 1 (25:1) in toluene led to essentially full conversion after 12 hours (−20 °C) or 10 minutes (room temperature).…”
Section: Activity Of Me2ga(ocph2me)(6-mes) (3 and 4) Me2m(oc6h4ome)(mentioning
confidence: 99%
“…As we were unable to isolate any stable alkoxide Me2InOR(6-Mes) complex, we focused on the activity of 1 in the ROP of rac-LA. Due to the reactivity of 1 towards CH2Cl2, which led to the almost quantitative and instant formation of [Me2Ga(μ-OCH2CH2OMe)]2 [9,35], no activity of 1 in the ROP of rac-LA in CH2Cl2, at −20 °C was observed. On the other hand, the polymerization of rac-LA with 1 (25:1) in toluene led to essentially full conversion after 12 hours (−20 °C) or 10 minutes (room temperature).…”
Section: Activity Of Me2ga(ocph2me)(6-mes) (3 and 4) Me2m(oc6h4ome)(mentioning
confidence: 99%
“…We have shown that dialkylgallium catalysts [R 2 Ga(m-OR)] 2 , which constitute a rare example of gallium catalysts for the polymerisation of lactide or other cyclic esters, 9 can catalyse the polymerisation of rac-LA to PLA in a controlled and stereoselective manner, 10 leading to a non-cytotoxic PLA. 6 Dialkylgallium alkoxides exhibit unique features with regard to the stereoselective polymerisation of rac-lactide (rac-LA).…”
mentioning
confidence: 99%
“…In this case the addition of a Lewis base (LB), such as pyridines or THF, to non-selective [R 2 Ga(m-OR)] 2 complexes resulted in the formation of heteroselective [R 2 Ga(m-OR)] 2 /LB catalytic systems offering tuneable heteroselectivity in the range of 0.5 o P r r 0.85 (P r = probability of racemo linkages in PLA). 10,11 On the other hand, the addition of N-heterocyclic carbenes or organosuperbases to [R 2 GaOR] 2 led to isoselective species, resulting in a facile stereoselectivity switch, 12 …”
mentioning
confidence: 99%
See 2 more Smart Citations